Concept art, minimal, arte povera, land art - Marzona, Egidio (Edition Cantz, 1990)
Ausstell Marzona, Egidio ; Sammlung ; Ausstellung ; Bielefeld <1990>
Literaturverzeichnis S. 266
Keywords: Ausstellungskatalog; Art; Modern; 20th century; Exhibitions; Art; Concept-art; Arte povera; Land-art; Minimal Art